The relationship between health literacy and the recovery rate of cardiovascular patients after bypass surgery - Anis Miri; Mohamad Ali Ghanbari; Ali Najafi (Mashhad University of Medical Sciences, 2016)
Background and objective: Health literacy includes a set of skills in reading, listening, analysis, decision-making and the ability to apply these skills to health situations aim of the study was to determine the relationship between health literacy and quickly improve cardiovascular patients after the bypass surgery is performed Methods: This applied study is an analytical survey. The study population included all patients had coronary heart bypass surgery in Mashhad Ghaem Hospital during the first half of 1394 was observed done at least one week before they had surgery. The questionnaire Functional Health Literacy in Adults and speed of recovery was self-made questionnaire that its validity and reliability was confirmed. Data collected by questioning the patient and using the software SPSS and Chi-Squar and Mann Whitney test were analyzed. Results: No significant differences between different age groups and gender in terms of health literacy exist. But between people with different education levels, there was a significant difference in terms of health literacy. Also, significant differences in postoperative complications and duration of hospitalization in the surgical ward, there Comparisons of health literacy. Conclusion: Most patients with inadequate health literacy and have a border. These patients need to understand and apply health information need further clarification and need to spend more time communicating with their medical staff for information in plain language to promote more understandable. Paper Type: Research Article.